ATG induction in renal transplant recipients: long-term hazard of severe infection is associated with long-term functional T cell impairment but not the ATG-induced CD4 cell decline - Weimer, Rolf; Ettrich, Maryam; Renner, Fabrice; Dietrich, Hartmut; Süsal, Caner; Deisz, Sabine; Padberg, Winfried; Opelz, Gerhard (Human immunology, 2014)
Background and methods - We showed previously that rabbit ATG induction induces a strong decrease of CD4+ T cells together with impaired in vitro IL-2 secretion up to 1year post-transplant. To further characterize long-term immunological effects of ATG induction 2 and 5years post-transplant, we used sensitive intracellular cytokine analysis in the same prospective study of 84 renal transplant recipients (ATG, n=44). - Results - A significantly increased frequency of severe infectious disease (HR=2.0, p=0.027) as well as suppressed T cell functions were found within 2years after ATG induction but not beyond (logistic regression (logreg): CD4 cell IL-10 responses, p=0.064; T cell proliferation, p=0.038). Impaired T cell proliferation at 2years was associated with occurrence of severe infection (p=0.017). Importantly, a strong and persistent decrease of CD4 cell counts (p<0.0005 at 5years) was independently associated with ATG induction (logreg p=0.002) but not related to functional CD4 cell impairment (helper activity/cytokine production) or an increased risk of infection. - Conclusions - Severe infection up to 2years after ATG induction was associated with impaired T cell proliferative capacity but not with the profound decline in CD4 cell counts that occurred after ATG induction and persisted up to 5years.